Tunicamycin-Induced Endoplasmic Reticulum Stress Promotes Breast Cancer Cell MDA-MB-231 Apoptosis through Inhibiting Wnt/β-Catenin Signaling Pathway. (15th July 2021) - You, Zhongsheng; He, Linkang; Yan, Nianlong
Abstract : Triple negative breast cancer (TNBC) has significantly threatened human health. Many aspects of TNBC are closely related to Wnt/ β -catenin pathway, and cell apoptosis induced by endoplasmic reticulum stress (ER stress) in TNBC may act as a potential target of non-chemotherapy treatment. However, how ER stress interacts with this pathway in TNBC has not yet been understood. Here, the tunicamycin and LiCl have been applied to MDA-MB-231. The related proteins' expression was measured by western blotting. Moreover, acridine orange/ethidium bromide (AO/EB) staining was applied to test the apoptosis degree of the cells, and cell viability was tested by MTT experiment. Then, we found the ER stress and apoptosis degree of MDA-MB-231 were induced after treatment with tunicamycin. Besides, tunicamycin dose dependently inhibited both Wnt/ β -catenin pathway and cells viability. Licl, an activator of Wnt/ β -catenin signaling pathway, could significantly inhibit cell apoptosis. In conclusion, our study found that the activation of ER stress could promote the MDA-MB-231 apoptosis by repressing Wnt/ β -catenin pathway, which provides some promising prospects and basic mechanism to the further research.